A Silver Roman Coin of Elagabalus and the Ship of State Tradition - Smith, Jonathan (Buried History: The Journal of the Australian Institute of Archaeology, 2022)
The significance of a scarce Roman coin type, RIC IV 188, an example of which was found in the Shapwick Hoard in 1998, has been largely overlooked. This paper analyses its iconography in the light of its Syrian-Roman context, the Graeco-Roman ‘Ship of State’ tradition, and other Elagabalus coins found at Shapwick. The conclusion is that RIC IV 188 is significant for presaging a theocratic coup by the Emperor Elagabalus and is the only primary source for his sea crossing from Asia to Europe in AD 219.